Overview of Family Characteristics of Stunting Toddlers - Diana Diana; Yulia Susanti; Dona Yanuar agus Santoso (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Toddler stunting includes chronic nutritional problems caused by many factors such as socioeconomic conditions, maternal nutrition during pregnancy, morbidity in infants, and lack of nutrition in infants. Family characteristics are one of the causes of stunting. The purpose of this study was to determine the description of the characteristics of families in stunting toddlers. This type of research is a quantitative, descriptive study with cross sectional approach. The sample of this research is 118 parents who have stunting children in the UPTD Patean Puskesmas Kendal City with random sampling technique. The research tools used were questionnaires and midline measuring devices. Data analysis uses univariate analysis of central tendency and frequency distribution. The results showed that the average age of parents: fathers 32.23 years with a range of 20 to 50 years, mothers 29.67 years with a range of 20 to 47 years, education of parents with elementary school education: fathers as much as 56 (47.5%) , 51 (43.2%) mothers, parents work as laborers: 82 fathers (69.5%), and 43 unemployed mothers (36.4%), the average parent's income is Rp. 2.234.755, have 2 children, 64 (54.2%), number of family members in one house: 4 (48.7%), family development stage: with 60 (50.8%) preschoolers, with type family: nuclear family as much as 65 (55.1%), the average age of toddlers 17.25 months with a range of 8 to 24 months, toddler height 68.47 cm, sex of toddler boys as much as 69 (58.5% ), a very short category of 90 (76.3%). Stunting in infants will have an impact on the lack of motor skills at school age and low productivity, low school grades, shorter height, and the risk of degenerative diseases in adulthood.